2003
DOI: 10.1093/wjaf/18.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Spring Versus Summer Spruce Stocktypes of Western Canada: Nursery Development and Field Performance

Abstract: This article summarizes information on the performance of spring versus summer spruce (Picea glauca, Picea engelmannii) stocktypes grown in western Canada. The spring planted stocktype is grown over one growing season in the nursery, hardened in late summer, goes through acclimation in the fall, lifted within a fairly broad window in late fall and early winter when it is considered winter-hardened, and then frozen-stored until planting in the spring This stocktype is planted across a fairly broad spring planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…Extending the planting season into the summer months can even improve the growth of planted Norway spruce (Helenius et al 2005;Luoranen et al 2006) seedlings because of the favorable temperature conditions for the growth and rooting of the seedlings. However, the risk for stress events, such as drought periods, is higher in the summer months than in spring, when the water content of the soil is naturally higher (Grossnickle et al 2000(Grossnickle et al , 2005Grossnickle and Folk 2003;Helenius et al 2005;Luoranen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extending the planting season into the summer months can even improve the growth of planted Norway spruce (Helenius et al 2005;Luoranen et al 2006) seedlings because of the favorable temperature conditions for the growth and rooting of the seedlings. However, the risk for stress events, such as drought periods, is higher in the summer months than in spring, when the water content of the soil is naturally higher (Grossnickle et al 2000(Grossnickle et al , 2005Grossnickle and Folk 2003;Helenius et al 2005;Luoranen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, to ensure the proper field performance of seedlings after planting, they must be in good condition at the time of planting (Helenius et al 2002;Grossnickle 2005). Actively-growing seedlings are more susceptible to drought and mechanical injury and early autumn frost damage, than seedlings planted while dormant (Deans et al 1990;Grossnickle et al 2000;Grossnickle and Folk 2003). On the other hand, drought risks in summer plantings may be reduced through the careful handling, storage, deep planting and watering of the seedlings (Helenius et al 2002(Helenius et al , 2005Luoranen and Viiri 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Scots pine (Pinus sylvestris L.), it is suggested that container seedlings are only planted in spring or early summer due to their growth rhythm and growing conditions in their typical planting sites in Nordic countries [3][4][5]. Similarly to the Nordic countries, summer plantings in July and August are also performed for different pine and spruce species in North America [6,7]. The extension of the planting season is a major prerequisite for enhancing the cost-competitiveness and facilitating the growth of the Nordic mechanized tree planting business [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fall lifted interior spruce seedlings are typically only freezer stored because there needs to be four to six months between lifting and spring planting [9,17,142]. Short term cooler storage is used in summer planting programs for hardened interior spruce seedlings [157]. Fall lifted seedlings are usually placed in frozen storage at -2 to -4 °C and as low as -6 °C [158] while still maintaining seedlings of high quality.…”
Section: Interior Sprucementioning
confidence: 99%